Inadvertent returns to theatre within 30 days (IRT30) of surgery: An educational tool to monitor surgical complications and improve our performance as surgeons. Issue 4 (5th October 2015) - Sukha, Anisha; Li, Elizabeth; Sykes, Tim; Fox, Anthony; Schofield, Andrew; Houghton, Andrew
Abstract : Purpose: – When a patient unexpectedly has to go back to the operating theatre, there is often a perceived problem with the primary operation. An IRT30 is defined as any patient returning to the operating theatre within 30 days of the index procedure. IRT30 has been suggested to be a useful quality indicator of surgical standards and surgeon performance. The purpose of this paper is to evaluate the usefulness of this validated tool, by assessing all IRT30 over a 12-month period. Learning points for individual surgeons, surgical subspecialty units and the clinical governance leads were reviewed. Design/methodology/approach: – Consecutive series of general and vascular surgical patients undergoing elective and emergency procedures between July 2012 and 2013. Prospective data collection of all IRT30s classified as Types 1-5 by a single-rater and in-depth discussion of Types 3-5 cases at the clinical governance meetings. The individual case learning points were recorded and the collective data monitored monthly. Findings: – There were 134 IRT30s. In total 84 cases were discussed: Type 3 ( n =80), Type 4 ( n =4) and Type 5 ( n =0). In total 50 cases were not discussed: Type 1 ( n =27), Type 2 ( n =23). Originality/value: – It is crucial that surgeons continue to learn throughout their surgical career by reflecting on their own and their colleague's results, complications and surgical performance. Analysing Types 3 and 4 IRT30s within the governance meetings has identified learning points related to both surgical technique and surgical decision making. By embracing these learning points, surgical technique and individual as well as group surgeon performance can be modified and opportunities for training and focused supervision created.